PENGARUH KEGIATAN PIK (PEMANTAPAN IMAN DAN KEISLAMAN) TERHADAP PENINGKATAN WAWASAN KEAGAMAAN DAN PERCAYA DIRI SISWA SD MUHAMMADIYAH 4 PUCANG SURABAYA - Rahmadiansyah, Khusnul Subekti (STAI Muhammadiyah Paciran Lamongan, 2025)
Concerned about students' lack of religious insight and self-confidence, SD Muhammadiyah 4 Pucang used PIK activities as a solution. This research was conducted because it was found that students still did not understand the application of religious sciences. Apart from that, it was also found that there was a crisis of self-confidence among students who tended to be introverted, did not want to express their opinions and were embarrassed to speak in public. The research method used is a quantitative method. The quantitative research approach uses a research instrument in the form of a questionnaire which is filled out by SD Muhammadiyah 4 students. From the results of the questionnaire, research results are found which are then narrated and supported with documentary evidence during data collection. PIK activities emphasize religious education and the habituation of students to worship as well as faith and morals. PIK activities include delivery of materials in class, guidance on the jurisprudence of worship in mosques and halls, and getting used to congregational prayers on time. Train students' interests, talents and courage by giving students the opportunity to appear as muezzins, religion lecturers, performers, and being dare to ask and answer during the material. Students' religious insight increased by 15% and students' self-confidence increased by 16% after participating in PIK activities. PIK activities (variable X1) have a significant effect on increasing religious insight (variable Y1) by 0.863. PIK activities (variable X1) have a significant effect on increasing student self-confidence (variable Y2) by 0.884. PIK activities (variable X1) have a significant effect on religious insight (Y1) and student self-confidence (Y2) amounting to 0.873